Needle-free Mental Incisive Nerve Block: In vitro, Cadaveric, and Pilot Clinical Studies - Qiman Gao (12107281) (2021)
The present study aimed to optimize Needle-Free Liquid Jet Injection (NFLJI) for Mental Incisive Nerve Blocks (MINB) and evaluate its clinical safety and feasibility. A MINB protocol was developed and optimized by series of NFLJI experiments in soft tissue phantoms and cadavers, then validated in two pilot Randomized Controlled Trials (RCT). The NFLJI penetration depth was found to be directly proportional to the supply pressure and volume. High-pressure NFLJIs (620 kPa or above) created maximum force and total work significantly greater than needle injections. Low-pressure NFLJIs (413 kPa), however, produced results similar to those of needle injections. Additionally, high-pressure NFLJIs created jet impingement pressure and maximum jet penetration pressure higher than low-pressure NFLJIs. Pilot RCTs revealed that high-pressure NFLJI caused a high risk of discomfort (60%) and paresthesia (20%); meanwhile, low-pressure NFLJI was less likely to cause complications (0%). The preliminary success rates of MINB from cadavers using NFLJIs and needles were 83.3% and 87.5%. In comparison, those from RCTs are 60% and 70%, respectively. To conclude, NFLJI supply pressure can be adjusted to achieve effective MINB with minimal complications. Furthermore, the cadaver study and pilot RCTs confirmed the feasibility for further non-inferiority RCT. Other Information Published in: International Journal of Pharmaceutics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijpharm.2021.121197